Development and Operational Status of Wind Power Forecasting System. Issue 4 (December 2014) - Aoki, Isao; Tanikawa, Ryoichi; Hayasaki, Nobuyuki; Matsumoto, Mitsuhiro; Enomoto, Shigero
SUMMARY Itochu Techno‐Solutions Corporation (CTC) and Tohoku Electric Power Co., Inc. have developed a system which predicts the wind power output in the control area of an electric power system in order to contribute to demand and supply control of the power system. Official operation of the system has been started after experimental operation during 3 years. Currently, the forecast information is used as reference information for electric power system operation in Tohoku Electric Power Co., Inc. In this paper, we describe the outline, operational status, and forecast accuracy of the system. We verified stable operation of the system and forecast accuracy of about 8% (intraday forecast) and 10% (day‐ahead forecast) by RMSE during experimental and official operation.